IDENTIFICAÇÃO DE SÍTIOS DE REPRODUÇÃO DE AEDES AEGYPTI COM AERONAVE REMOTAMENTE PILOTADA (ARP) - Antonio Pereira, Matheus (2021)
A drone and its flight accessories are called Remotely Piloted Aircraft System (RPAS - Remotely Piloted Aircraft System), being a tool with a wide range of applications in several areas. The research explored new possibilities for the use of RPAS with a focus on the diagnosis and monitoring of breeding sites for Aedes aegypti. For this, objects considered as potential breeding grounds for mosquito larvae were distributed in environments that allowed greater or lesser visual detection of targets (packages / containers) in four environments: soil covered with dry grass, exposed soil, soil covered with low grass. and soil covered with tall grass. We use RPAS, Phantom 4 Pro with an Ipad Mini 4 mobile device and the DJI GO program for flights. We fly over targets for photographic recording at four heights from the ground (20m, 30m, 60m and 80m). The visual detection of the targets was carried out by a group of 10 people called a jury. The Jury assessed the greater or lesser probability of target detection, depending on three variables: type of target, type of environment and height of aerial photography. Photographs taken at a height of 30 meters represented the largest number of targets identified (30% of the targets). The most identified targets were tires, pet bottles, cans of beer and cans of paint. The least identified were colored plastic canisters and beer bottles. The research helped to improve operational procedures for controlling and combating endemics and epidemics, which may identify possible mosquito breeding sites through RPA, monitoring areas of difficult access that pose a risk to people's physical integrity.